Dilema Perkawinan Adat Sumbawa di Masa Pandemi Covid-19 - Fatihatul Anhar Azzulfa (State Islamic University (UIN) of Sunan Ampel, 2020)
The procession of traditional marriage is a custom in the community that contains all rituals and require the implementation that must done by many people. The dilemma that occurs in the people of Sumbawa is a problem that must be faced together between the community and the government. This paper tries to explore and examine how the practice of traditional Sumbawa marriage when the Covid-19 pandemic took place in Brang Biji Village, Sumbawa District, Sumbawa Besar Regency. This research is a field research using descriptive analytical method. In this case, the local government has issued a policy during a pandemic Covid-19 to any person who performs his business to always implement health protocols. Meanwhile, the community understands that the traditional marriage procession must always be carried out and the pandemic is not a barrier. The obligation to carry out a traditional marriage procession is not regulated in terms of harmony or marriage conditions, but this customary procession does not contradict Islamic law. Marriage will remain valid if it is carried out in harmony and legal conditions of marriage according to Islamic law without carrying out the traditional procession in marriage. The government should provide an understanding to the community that during the Covid-19 pandemic, traditional marriage processions brought more mafsadah than benefits. Traditional procession becomes less meaningful if it ultimately brings bad consequences to himself or others